Association between living alone and all-cause mortality of young and middle-aged patients with acute myocardial infarction: analysis of the China Acute Myocardial Infarction (CAMI) registry - Yu Jiang; Jin-Gang Yang; Hai-Yan Qian; Yue-Jin Yang (BMC, 2024)
Abstract Background Lack of social support is a known predictor of the prognosis after acute myocardial infarction (AMI). Although as a common factor associated with social support, there are limited data on long-term prognostic impact of living status in young and middle-aged patients with AMI. Methods We analyzed data from the China Acute Myocardial Infarction (CAMI) Registry, consecutive AMI young and middle-aged patients admitted at 108 hospitals in China between January 2013 and September 2014 were included. Eligible patients were assigned to living alone and not living alone groups based on their living status. The primary endpoint was 2-year all-cause mortality. The secondary endpoints included in-hospital mortality and 2-year major adverse cardiac and cerebrovascular events (MACCEs; a composite of all-cause mortality, MI, or stroke). Multilevel logistic and multilevel Cox regression models were used to evaluate the effect of living status on short-term and long-term outcomes. Results A total of 8307 consecutive AMI young and middle-aged patients were included, 192 (2.3%) patients were living alone. Of the analyzed patients, living alone was associated with 2-year all-cause mortality and MACCEs among all analyzed patients after multivariate adjustment (adjusted hazard ratio [HR] = 2.171 [1.210-3.895], P = 0.009; adjusted HR = 2.169 [1.395-3.370], P = 0.001), but not with poorer in-hospital mortality. Conclusions The analysis suggested that living alone was associated with both 2-year all-cause mortality and MACCEs in AMI young and middle-aged patients but did not show an extra effect on the in-hospital mortality after covariate adjustment. Trial registration Trial registration number: NCT01874691; Registered 31 October 2012.